ANALISIS PENGARUH METODE VACUUM BAG TERHADAP GEOMETRI SAYAP UAV SKYWALKER - Ikbal Rizki Putra; Ferry Setiawan; Sehono; Angger Bagus Prasetiyo (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2023)
This research focuses on manufacturing composite wings using the vacuum bag process. The vacuum bag method is used because it can reduce manufacturing time and improve the quality of the final product. This study aims to determine the impact of the vacuum bag method on the geometry between the design stages and the final results of the UAV wing. Differences in design geometry and final results are calculated by measurement. The effects of variations in thickness and loading were estimated by modeling simulations with Fusion360 Software. The geometry of the design stage and the final result did not have a significant change, with a difference of 10% in thickness, 2.45% in wing length, and 0.80% in wing width. For deformation, it can be concluded that the increase in thickness and loading is directly proportional to the magnitude of the deformation that occurs. The greater the value of thickness and loading, the greater the deformation that occurs.